Assessment of Exported Tea Quantity by Soft Computing Model - Roy, A; Kundu, S; Bhattacharya, J; Singh, D; Sahana, S; Nath, Ira (International Journal of Computer Sciences and Engineering, 2025)
Assessment plays a major role in the field of prediction. If the Assessment cannot be selected properly, the prediction information becomes incorrect and this scope of work of futuristic planning becomes lost. Therefore it is needed to select an appropriate technique for the purpose of forecasting. A lot of soft computing model is being used in various application systems for the purpose of forecasting. The performance of fuzzy logic, in the field of soft computing, is being examined for the purpose of Assessment on the basis of average error. Here an effort is being used to select the proper soft computing technique to predict the futuristic information of quantity of exported tea to be exported in near future. Initially, the concept of least square base linear equation has been applied and therefore after concept of Fuzzy logic with Membership functions of soft computing has been used to optimize the error.